Effect of graphene sheets on the physico-chemical properties of nanocrystallite ceria - Elena A. Trusova; Ivan Ponomarev; Evgeny Shelekhov (Royal Society Open Science)
Currently, replacing expensive and short-lived materials for supercapacitors based on RuO2 with more cost-effective and high-performance materials that remain operational after a large number of cycles is a challenge. Cerium-based materials are the most attractive alternative because of cerium’s ability to quickly change oxidation state. This work proposes the synthesis of nanostructured graphene–ceria composite and studies its morphological features arising under the impact of oxygen-free graphene. The mechanism of formation of nano-ceria crystallites when the sol–gel transition occurs on the surface of graphene sheets is also considered. It has been proven that the introduction of 0.5–0.6 wt% graphene sheets into nano-ceria ensures the preservation of its single-phase state, while simultaneously increasing its dispersion. Using the dilatometry method, it has been determined that uniformly distributed sheets of oxygen-free graphene lead to a decrease in temperature of the beginning of composite sintering by 175°C compared with pure nano-ceria and increase the shrinkage value by two times, which, in turn, should promote better sintering. This study fills a gap in the synthesis and characterization of oxygen-free graphene composites, promising raw materials for small devices and large power plants.